Template synthesis of porous hierarchical Cu2ZnSnS4 nanostructures for photoelectrochemical water splitting. (11th January 2021) - Chen, Yubin; Xia, Hongyu; Zhang, Wenshuai; Zheng, Wenyu; Feng, Xiaoyang; Jiang, Jiangang
Abstract: Environmentally friendly and low-cost Cu2 ZnSnS4 (CZTS) is a promising light absorber for photoelectrochemical (PEC) hydrogen production from water splitting due to the earth-abundant elements, high absorption coefficient, and narrow bandgap. Herein, the hierarchical CZTS film with porous nanostructures was successfully synthesized by a template method. The hierarchical CZTS film was composed of flower-like particles, which were assembled with thin CZTS nanosheets. Macropores were generated owing to the aggregation of flower-like spheres, and mesopores were formed from the stacking of CZTS nanosheets. Compared to the dense CZTS film, the porous hierarchical CZTS film showed a much higher PEC property for water splitting. The improved performance could be attributed to three merits of the porous hierarchical morphology: enhanced light absorption, improved charge separation and transfer, and enlarged electrochemically active surface area. This study provides a useful idea to design efficient semiconductor photoelectrodes for water splitting with delicately controlled morphology. Highlights: The porous hierarchical Cu2 ZnSnS4 film was prepared for PEC water splitting. Flower-like Cu2 ZnSnS4 particles assembled with thin nanosheets were generated. The porous hierarchical Cu2 ZnSnS4 film showed a higher property than the dense film. The improved property was ascribed to three merits of porous hierarchical morphology.